Sensitive Detection of Sulfide Ion Based on Fluorescent Ionic Liquid–Graphene Quantum Dots Nanocomposite - Qiu, Guanhua; Han, Yaoqi; Zhu, Xiaoqi; Gong, Jiawei; Luo, Tao; Zhao, Chang; Liu, Junjie; Liu, Jiyang; Li, Xiang (Frontiers in Chemistry, 2021)
Sulfide ions (S2-), that are widely distributed in biological and industrial fields, are extremely toxic and pose great harms to both ecological environment and human health. However, the currently reported fluorescence sensing of S2- ions generally based on indirect detection strategy using S2--recovered fluorescence of fluorophore that is firstly quenched by metal ions. Selective fluorescent probe which enables direct and sensitive detection of S2- ion is highly desirable but remains as great challenges. Herein, we demonstrate one-step preparation of fluorescent ionic liquid-graphene quantum dots (IL-GQDs) nanocomposite, which can act as fluorescent probe for direct and sensitive detection of S2- ion. The IL-GQDs nanocomposite is easily synthesized via facile molecular fusion of carbon precursor and in situ surface modification of GQDs by IL under hydrothermal condition. The as-prepared IL-GQDs nanocomposite has uniform and ultrasmall size, high crystallinity, and bright green fluorescence (absolute photoluminescence quantum yield of 18.2%). S2- ions can strongly and selectively quench the fluorescence of IL-GQDs because of the anion exchange ability of IL. With IL-GQDs nanocomposite being fluorescent probe, direct and sensitive detection of S2- is realized with a linear detection range of 100 nM - 10 μM and 10 μM - 0.2 mM (limit of detection or LOD of 23 nM). Detection of S2- ions in environmental river water is also achieved.